Assessing the Importance of Training Opportunities in Sterilization and Disinfection of Patient Care Items: A Systematic Review - Alshahrani, Abdullah Saed; Al Shehri, Ahmed Salem; Al Garni, Ahmed Mohammed; Althobaiti, Fahad Shuayl (Journal of Ecohumanism, 2024)
Background: Effective sterilization and disinfection of reusable medical instruments are foundational to infection prevention and patient safety. Despite established protocols, compliance among healthcare staff varies widely, often due to inadequate training. This review aims to assess the impact and characteristics of training programs focused on sterilization and disinfection practices among healthcare workers. Methods: A systematic review was conducted following PRISMA 2020 guidelines. Searches were performed in PubMed, Scopus, Embase, Web of Science, and Google Scholar. Eligible studies included those evaluating training interventions for healthcare workers engaged in sterilization and disinfection, published between 2010 and 2024. Narrative synthesis was used due to heterogeneity in methods and outcomes. Results: Fifteen studies met inclusion criteria. Training programs—ranging from brief workshops to comprehensive systems-based interventions—improved knowledge (average increase of 25–30%), compliance (up to 34% improvement), and reduced contamination and sterilization errors. Quarterly training was associated with better retention than annual sessions. Integration with broader quality initiatives like 6S management further enhanced efficiency. Conclusion: Training is a vital component of IPC and significantly improves sterilization and disinfection outcomes. Sustainable improvements require institutional support, continuous reinforcement, and alignment with international standards. Further studies should assess long-term impact and explore digital or low-resource adaptable training formats.